OPTIMIZATION OF PRIMARY SOMATIC EMBRYOGENESIS INDUCTION OFCOCOA (Theobroma cacaoL.) THROUGH THE ADDITION OF PHENOLICCOMPOUNDSUPPRESSANT MATERIALS - Priandani, Putri Oktaviana; Pancaningtyas, Sulistyani; Ubaidillah, Mohammad (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
Somatic embryogenesis is a propagation technique in which explants form somatic embryos. The percentage of primary somatic embryo formation in cocoa tends to be low due to the significant secretion of phenolic components in flower explants, thereby reducing the conversion rate of explants into embryos. This is indicated by browning that occurs in explants or the culture medium. The purpose of this study was to optimize primary somatic embryogenesis induction in cocoa through the addition of several types of phenolic compound suppressor materials to the culture medium. Staminodia explants were grownon DKW medium with factorial treatment: various phenolic compound suppressing materials (control; 300 mg L-1PVP; 15 mg L-1silver nitrate; 12 mg L-1melatonin; 300 mg L-1ascorbic acid) and cocoa cultivars (MCC-02 and ICCRI-09). The results showed that each material treatment produced a different response in suppressing phenolic compounds in each cultivar. The melatonin treatment resulted in the lowest percentage of browning intensity, which also had the best impact on morphology, callus size, wet weight,and the percentage of live explants.